A Conceptual Study of Al-Qur’an and Islamic Psychology for Cryptocurrency Scams - Johnderose, Ahmad Qolbi Zidan; Puspitasari, Niken Sylvia; Madany, Averosian Sophia (Institut Muslim Cendekia, 2026)
Fraud in cryptocurrency investment is a serious moral and economic deviation within the contemporary digital economy, which impacts the spiritual and psychological well-being of individuals. The Qur'an explicitly prohibits fraud and the unlawful acquisition of wealth (al-bāṭil). This study aimed to develop a conceptual framework by integrating Qur'anic ethical values with principles Islamic psychology to understand the dynamics of cryptocurrency scams, including the behavioural motivations of perpetrators and the psychological conditions of victims. The research used descriptive qualitative method based on a literature review, employing a Thematic Interpretation (tafsīr mauḍū‘ī) approach and Islamic psychology analysis. The results of the study showed that perpetrators of cryptocurrency scams were driven by the dominance of nafs al-ammārah bi al-sū', which is rooted in greed and materialism, while victims were vulnerable due to ignorance and weak spiritual self-control. The Qur'anic framework offers solutions through tazkiyatun nafs, muhasabah, and muraqabah as the ethical foundation for dealing with the complexities of modern digital finance, while contributing to the Islamisation of science.